Pengaruh Pemasaran Media Sosial Terhadap Purchase Intention Asuransi Syariah di Indonesia - Dini Amalia Putri (Faculty of Islamic Religion, Universitas Muhammadiyah Sumatera Utara, 2020)
Indonesia has a large potential as a potential market share of Islamic insurance. However, in reality the large muslim population does not necessarily guarantee the large market share of Islamic insurance in Indonesia. Based on AAJI data, insurance users in Indonesia have only reached 7.5%, and only around 5% of that number uses sharia insurance. The low awareness, knowledge and exposure to sharia insurance is the reason for the lack of sharia insurance participation rates. It can be seen from the low literacy rate of sharia insurance in Indonesia that only reached 2.51%. With the rise of the use of social media in Indonesia, Islamic insurance operators use social media as a means of bridging communication between them and consumers. This study seeks to find out how the influence of social media marketing on buying interest in Islamic insurance. Analysis of data from the results of a survey of 324 respondents using Lisrel-SEM found that social media marketing and product compliance with sharia rules had a positive effect on purchase intention through an intermediary attitude towards sharia insurance. While social media marketing compliance to sharia rules has proven to have a negative effect on attitudes towards sharia insurance.